A Schizo-Poetic Inquiry of a First-Year Doctoral Experience - Roberts Bucca, Kate (Art/Research International)

(untitled) (University of Alberta, 2023)
Undertaking a doctoral program is a significant commitment involving sustained effort as an individual engages in academic work and scholarly identity formation. As a graduate student with a psychiatric disability, I face an added layer of challenge: dealing with symptoms as I navigate an academic system that is not designed for bodyminds like mine. This poetry and visual art collection offers a glimpse into my experience as a first-year doctoral student with schizoaffective disorder1 as I navigated Zoom classrooms, considered academic timelines and campus mental health awareness week, and wrestled with symptoms during the summer session. Through a schizo-poetic and visual inquiry informed by disability poetry and schizo-poetics, I present an embodied, multi-sensory exploration to highlight similarities and differences in the experiences of doctoral students with mental illness and their neurotypical peers, as well as to expand the conversation around disability and academia.